Modification in HCM Delay Model for Roundabout for Mixed Traffic Conditions - A Pilot Study - Asir Khan; Ashish Dhamaniya; Shriniwas Arkatkar (Communications - Scientific letters of the University of Zilina, 2022)
Roundabouts have proven to be an effective intersection design method for smooth traffic flow movements and improved safety. Previous studies show that VISSIM, commercial traffic simulation software, can be used as a proficient tool for modeling and efficiently analyzing roundabouts. This paper focuses on developing a methodology for modeling roundabouts in India using VISSIM. Three typical roundabouts were chosen from the northern part of India. Calibration and validation of the model were performed to ensure the correctness of the model. The average delay and volume to capacity ratio (v/c ratio) were compared for developing the level of service (LOS) thresholds for Indian conditions. The thresholds are compared with existing guidelines provided by the HCM 2010 and AUSTROADS. In addition, the methodology for determining modification factors for applying HCM 2010 delay model in Indian traffic conditions is defined.